Biosynthesis of selenium nanoparticles by Aspergillus niger - Noorbatcha, Ibrahim Ali; Rosena, Norol; Mohd. Salleh, Hamzah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Nanoparticles can be synthesized by biological, chemical and physical methods. There are several disadvantages of physical and chemical synthesis methods which include release of hazardous and toxic effluents and higher cost of production. The use of microbial factories for the production of nanoparticles is an emerging field with immense potential. The synthesis of nanoparticles using microbes has not been explored for the production of selenium nanoparticles. In this work Aspergillus niger (A. niger) was challenged with sodium selenite solution at different concentrations. After several screenings, the production of selenium nanoparticles was obtained by treating the biomass of A. niger with 1 mM concentration of sodium selenite at 37°C. An intense red color and the UV-vis spectrophotometer absorbance maximum at 226 nm wavelength were observed within 24 hours, indicating the formation of selenium nanoparticles. Further analysis by FESEM characterization showed spherical selenium nanoparticles with 60-100 nm size range. These results indicate that A. niger can be used as a versatile microbial factory for the synthesis of selenium nanoparticles.